Low Residual CBF Variability in Alzheimer’s Disease after Correction for CO2 Effect - Rodell, Anders B.; Aanerud, Joel F.; Braendgaard, Hans; Gjedde, Albert (Frontiers in Neuroenergetics, 2012)
We tested the claim that decline of inter-individual CBF variability in Alzheimer’s disease (AD) is pronounced when the variability from changes of arterial CO2 tension (PaCO2) is eliminated. Specifically, we tested whether the variability of CBF in brain of patients with AD differed significantly from brain of age-matched healthy control subjects (HC). To eliminate the CO2-induced variability, we developed a novel and generally applicable approach to the correction of CBF for changes of PaCO2 and applied the method to positron emission tomographic (PET) measures of CBF in AD and HC groups of subjects. After correction for the differences of CO2 tension, the patients with AD lost the inter-individual CBF variability that continued to characterize the HC subjects. The difference (delta K1 ) between the blood-brain clearances (K1) of water (the current measure of CBF) and oxygen (the current measure of oxygen clearance) was reduced globally in AD and particularly in the parietal, occipital, and temporal lobes. We then showed that oxygen gradients calculated for brain tissue were similar in AD and HC, indicating that the low residual variability of CBF in AD may be due to low functional demands for oxidative metabolism of brain tissue rather than impaired delivery of oxygen